ASSESMENT OF PHYSICAL ACTIVITY ON ACADEMIC PERFORMANCE OF SCHOOL CHILDREN - Tripathi, Himanshu (International Journal of Research -GRANTHAALAYAH, 2016)
There is a need to find out the association between school-based physical activity, including physical education and academic performance among school-aged youth. To better understand these connections, this research paper first finds out the independent variables upon which academic performance depends. Study is from a range of physical activity contexts, including school-based physical education, recess, classroom-based physical activity and extracurricular physical activity. In his attempt researcher studied 120 students from 04 CBSE schools of Bikaner District, Rajasthan. He uses Physical Activity Questionnaire for Children (PAQ-C) to find out physical activity performance of students, examination/ test scores to find out the academic achievement and stroopcolour word task to find out the academic performance which includes cognitive dimension also.